Sexual Revolutions
XIII, 292 p.
Keywords: Sexual Revolutions explores the sexual revolution of the late twentieth century in several European countries and the USA by engaging with themes from sexual freedom and abortion to pornography and sexual variation. This work discusses the involvement of youth, feminism, left, liberalism, arts, science and religion in the process of sexual change.